Global and national actions to prevent trade in substandard and adulterated medicines. - Richard Wilder; Sam Halabi; Lawrence O Gostin (PLOS Global Public Health)
Recent mass-poisoning events caused by substandard medicines placed in global markets raise the question as to what more can be done to stop it. Efforts have been underway for years at the World Health Organization and other multilateral fora, such as the National Academies of Medicine in the U.S. While these efforts have led to improvements, several gaps remain which, unless addressed, will allow this problem in international trade to continue. Some countries have failed to implement the standards set by the WHO by not fully empowering national regulatory agencies to lead national efforts. Further, some countries do not fully exercise their responsibility under WHO standards to confirm that the information in documents accompanying internationally traded medicines is complete, accurate, and current. It is time to revisit international standards in this area to determine the causes of these problems and to address them.